TINGKAT BURNOUT STAF PERPUSTAKAAN BADAN PERPUSTAKAAN DAN ARSIP DAERAH (BPAD) PROVINSI DKI JAKARTA - Riya Fatmawati; Sefri Doni (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
This is a quantitative research which talks about burnout level of library service’s staff at BPAD DKI Jakarta library. The instrument of this research is “Maslach Burnout Inventory (MBI)”. The data was collected by spreading questionnaires to 30 respondents. The research was done to measure three variables of burnout, they are physical saturation, emotional saturation, and the achievement of self. The result shows that 7% staff of BPAD library service have been identified as burnout. The burnout were particularly caused by physical saturation. According to MBI standard, the burnout level of library service’s staff is on the first level. It means that the library service’s staff could manage stress as well.